Teachers' Voice Of Using Crossword Puzzle Games To Improve Students' Vocabulary (RETAIN, 2023)
Abstract One technique that can be used by teachers in the teaching and learning process to create learning that is fun and quickly understood is to use game techniques. With this technique, teachers can create comfortable classrooms for students so that students can increase their desire to learn English. One of the important things in learning English is vocabulary. Teachers can use game techniques in teaching student vocabulary to improve student vocabulary and make the learning process fun. One game that can be used by teachers to improve students' vocabulary is a crossword puzzle game. Crossword puzzles have a positive impact on students; students feel happy and interested in learning English, and students can add vocabulary according to the material at that time. The researcher wants to know the teachers’ voice of using crossword puzzles to improve students' vocabulary. This research is qualitative research with five high school teachers in Mojoagung and Mojokerto as participants. In this study, the researcher used an open-ended questionnaire using Google Forms. This study used semi-structured interviews via WhatsApp. The results of the study show that teachers can use crossword puzzle games in teaching to improve students' vocabulary. Teachers use various types of crosswords according to their needs, while the types of crosswords are oral, picture, and object crosswords. The most important thing from this research is the advantages of using crossword puzzles, which can improve students' vocabulary. Crossword puzzles have challenges when applied in teaching, and these challenges can be seen from internal and external challenges. Keywords: Teacher’s Voice, Crossword Puzzle, Vocabulary